Asset Pricing in Indian Securities Market: The Role of Beta and Book to Market Equity Ratio - Manjunatha, T. (Indian Journal of Finance, 2008)
The study tests whether beta, as envisaged in CAPM, and book-to-market equity ratio ln(BE/ME), as envisaged in the Fama and French (FF) model, are the determinants of the security and portfolio returns. Further the study also tests whether the intercept of the CAPM is equal to the risk-free rate of return as envisaged in the standard form of the theory. When percentage returns are considered, ln(BE/ME) explains the variation in security returns in univariate regression while the combination of beta and ln(BE/ME) explain this variation in multiple regressions. However, these variables do not explain variations in security returns when log returns are considered. The overall results, based on percentage and log returns, show that the intercept is equal to the risk-free rate of return but the beta and ln (BE/ME) factors do not explain the variation in individual security returns and portfolio returns in Indian capital market. Therefore, the factors in the FF model that are important in western market in determining the security/portfolio returns do not emerge as the important factors in the Indian market. The results of this paper help in understanding the significance of beta and book-to-market equity ratio in asset pricing in Indian market.